2016
DOI: 10.1017/s2078633616000114
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis for morphological traits of the Hamra goat population in two regions of Morocco

Abstract: SummaryThe goal of this study was to characterize the Hamra goat population and to determine if Hamra goats of Beni Arouss and Rommani regions belong to the same population. Eleven morphometric traits of 157 Hamra animals (94 from Beni Arouss and 63 from Rommani) were used for this study. Overall, heart girth, body length, height at withers (HaW), height at rump (HS), chest depth (ChD), pelvis width (PW), chest width (CW), cannon circumference, head length (HeL), head width (HeW) and horn length (HL) of Hamra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
3
2
Order By: Relevance
“…High KMO values were also reported for cattle (Pundir et al, 2011;N'Goran et al, 2015N'Goran et al, , 2018. Whereas this result was slightly lower than that of Djallonké sheep reported by Birteeb et al (2012;, and that of Uda sheep reported by Yakubu and Ibrahim (2011) Findings in this study are in the range of those reported in Niger by Marichatou et al (2014) extracted for goat two factors to explain 67.8 % of the total variance, but lower than those reported by Hilal et al (2016) for the Hamra goat (73.5%) in Morocco where four factors were extracted to explain the total variance.…”
Section: Discussioncontrasting
confidence: 82%
“…High KMO values were also reported for cattle (Pundir et al, 2011;N'Goran et al, 2015N'Goran et al, , 2018. Whereas this result was slightly lower than that of Djallonké sheep reported by Birteeb et al (2012;, and that of Uda sheep reported by Yakubu and Ibrahim (2011) Findings in this study are in the range of those reported in Niger by Marichatou et al (2014) extracted for goat two factors to explain 67.8 % of the total variance, but lower than those reported by Hilal et al (2016) for the Hamra goat (73.5%) in Morocco where four factors were extracted to explain the total variance.…”
Section: Discussioncontrasting
confidence: 82%
“…Although there was no significant effect of gender on depth index and proportionality index, female Cyprus Native Hair Goats tended to have higher values for these traits. These findings were in agreement with those of Hilal et al [30], suggesting that sex must be an important factor of variation in body weight and morphological indices in indigenous Goat breeds.…”
Section: Morphological Indices In Cyprus Native Hair Goats Are Given ...supporting
confidence: 93%
“…Multivariate discriminant analyses of morphological traits have been reported, in several previous morphometric studies, to be effective for a precise and objective discrimination of different population of cattle [22][23][24][25][26][27][28], goat [29][30][31][32][33][34], sheep [16,[35][36][37], horses [38] and camel [39].…”
Section: Introductionmentioning
confidence: 99%